Retraction notice to “Eco-geomorphic interactions and planform adjustments of the transboundary Rapti River (2004–2024): Insights from remote sensing and google earth engine analysis” [Geomorphology 506 (2026) 110330] - Ankur Kumar; Govind Pandey; Ravindra Vitthal Kale (Geomorphology, 2026)

Eco-hydraulic role of native Indian vegetation in wetland bank stabilization and water quality improvement: A numerical and bioengineering perspective - Ashish Kumar Singh; Govind Pandey; Chandra Shekhar Prasad Ojha; Rajendra Prasad Singh (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Impact of coronal malalignment and implant design on stress-related malleolar fracture risk following total ankle replacement - Govind Upadhyay; Gaurav Kumar Sharma; Rajesh Ghosh (Next Research, 2026)

Spatial Modeling of Soil Organic Carbon in Northeast Thailand Using Machine Learning Techniques - Nitiwat Wongchanla; Subhankar Debnath; Jai Govind Singh; Avishek Datta; Sushil Kumar Himanshu (Journal of the Indian Society of Remote Sensing, 2026)

Structural and Antioxidant Changes in Roots Contribute to Whole-Plant Desiccation Tolerance in Oeosporangium elegans - Hosahalli Somasundara Reddy Rudresh; Hulikall Shivashankara Santhosh Kumar; Sudisha Jogaiah; Ramasandra Govind Sharathchandra (Journal of Plant Growth Regulation, 2026)

RETRACTED: Eco-geomorphic interactions and planform adjustments of the transboundary Rapti River (2004–2024): Insights from remote sensing and google earth engine analysis - Ankur Kumar; Govind Pandey; Ravindra Vitthal Kale (Geomorphology, 2026)

Multiple gene detection of ‘Candidatus Phytoplasma australiasiaticum’ related strain associated with stem fasciation in Brassica napus L - Shivani Gupta; Ashok Kumar Singh; Deepak Kumar; Ravinder Kumar; Govind Pratap Rao (Indian Phytopathology, 2026)

Deterministic strain engineering through growth-driven stacking in twisted bilayer MoS2 - Pukhraj Prajapat; Vaibhav Kandwal; Jayalekshmi U.J.; Aditya Kushwaha; Neeraj Goel; Ajay Kumar Shukla; Govind Gupta (Chemical Engineering Journal, 2026)

Estimating Soybean Production at Multiple Scale Using Remote Sensing Based Crop Model and Data from Both Optical and Microwave Sensor - Rojalin Tripathy; Nita Bhagia; Mukesh Kumar; Bimal Kumar Bhattacharya; Govind Bairagi; Indal Ramteke (Journal of the Indian Society of Remote Sensing, 2026)

An investigation of the global responses of the thermal field of the MLT region to the ‘Severe’ geomagnetic storm of 10–11 October 2024 - Govind Narayanan Kunnath; Navin Parihar; Chinmaya Nayak; Alok Taori; Anand Kumar Singh; Shailendra Saini; Prasant Kumar Tiwari; Ashok Priyadarshan Dimri (Advances in Space Research, 2026)

Development of vitamin D biofortified rice: the way forward - Tapan Kumar Mondal; K. Arun; Diptasree Kumar; Pradeep Kumar; Govind K. Makharia; Tilak Raj Sharma (Journal of Plant Biochemistry and Biotechnology, 2026)

Early Permian peatland dynamics at the northern margin of Gondwana: multi-proxy insights from the Bhareli formation, Siang Window, Eastern Himalaya - Dipjyoti Borsaikia; Govind Kumar; Mousumi Gogoi; Amiya Shankar Naik; Thadoju Satish Kumar; Sarat Phukan (International Journal of Earth Sciences, 2026)

Differential Metabolic and Transcriptional Responses of PBMCs to Blastocystis sp. Subtypes in Chemotherapy-Treated Colorectal Cancer Patients - Muhammad Mirza Halimi; Deviga Genasan; Arutchelvan Rajamanikam; Deepa Anbazhagan; Vetriselvan Subramaniyan; Suresh Kumar Govind; Umah Rani Kuppusamy; Rohit Gundamaraju; Vinoth Kumarasamy (Acta Parasitologica, 2026)

Integrated multi-index tectono-geomorphic analysis of the transboundary Rapti River Basin using multi-resolution DEMs - Ankur Kumar; Govind Pandey; Ravindra Vitthal Kale (Innovative Infrastructure Solutions, 2026)

A critical review and analysis of fly ash-based one-part geopolymer - Pushpender Kumar; Govind Gaurav; Needhi Kotoky; Shivang Shekhar (Innovative Infrastructure Solutions, 2026)

A ∼1.6 Ga accretionary event in the polymetamorphic Lesser Himalaya, India: Insights into late-stage assembly of the Columbia supercontinent - Mallickarjun Joshi; Biraja P. Das; Shubham Patel; Daniel Pastor-Galán; Naresh C. Pant; A. Krishnakanta Singh; Govind Oinam; Alok Kumar; Ankit Kumar (Precambrian Research, 2026)

Climate-resilient agriculture strategies to address the challenges of agri-food security and climate change - Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Shubham Durgude; Suneel Kumar; Illathur R. Reddy; S. Pazhanisamy; et al. (Field Crops Research, 2026)

Fe-rich NASICON cathode with enhanced energy density and structural stability enabled by Fe/Mo co-doping-induced electronic coupling - Sheetal Gupta; Suporna Bhowmik; Khushwant Singh; Neha Chaudhary; Govind Kumar Maurya; Dhirendra K. Rai (Chemical Engineering Journal, 2026)

Landslide susceptibility mapping and kinematic analysis in Bachchangad catchment, Uttarakhand, India: a comparative study using machine learning benchmark classifiers - Khyati Gupta; Aasif Ibni Ahad; Devendra Singh Rawat; Syed Kaiser Bukhari; Bikash Kumar Ram; Govind Singh Rawat; Vikas Yadav; Ashutosh Kainthola; Tariq Siddique; Mohammad Azarafza (Natural Hazards, 2026)

Arsenic Bioaccumulation in Cattle Naturally Exposed to Geogenic Groundwater Contamination in the Middle Indo-Gangetic Plains of Bihar - Ravi Kumar; Rashmi Rekha Kumari; Nirbhay Kumar; Archana; Ramesh K. Nirala; Kumari Anjana; Govind Kumar Choudhary; Tapan Kumar Mandal; Pankaj Kumar (Bulletin of Environmental Contamination and Toxicology, 2026)

Climate-resilient agri-food systems: analyzing yield trends and overcoming adoption barriers - Shubham Durgude; Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Dinesh Chand Meena; Suneel Kumar; Illathur R. Reddy; et al. (Environment, Development and Sustainability, 2026)

Physiological, Biochemical, and Molecular Responses During Grafting in Horticultural Crops - Narayan Lal; Vikas Ramteke; Garima Diwan; Pragya Singh; Nisha Sahu; Debashish Hota; Maneesha S.R.; Nirmal Kumar Meena; Kapil Mohan Sharma; Govind Balasaheb Shiurkar; Ganesh Maske; N. R. Rangare (Plant Molecular Biology Reporter, 2025)

Impact of Micronutrients on Flowering, Yield, and Fruit Quality Attributes of Strawberry (Fragaria × ananassa Duch) cv. Camarosa Under Open Field Conditions - Yogendra Singh; Govind Gupta; Ujwal Virkhare; Mukul Kumar; Prajwal Nimbulkar; Suman Kumari; Yogita Chouhan; Harshit Jangid; Suresh Chandra Gurjar; Om Prakash Lodha; Deepak Kher (Applied Fruit Science, 2025)

Geochemical and petrological characteristics coupled with stable isotope of the Permian Gondwana coals from Tatapani–Ramkola Coalfield, Son–Mahanadi Basin, India: Insights for paleodepositional and paleoclimate conditions - Neeraj Kumar Upadhayay; Amiya Shankar Naik; Shweta Rai; Prakash K. Singh; Alok Kumar; Afikah Rahim; Mohammed Hail Hakimi; Govind Kumar; Pramod Kumar Rajak (International Journal of Coal Geology, 2025)

Development and assessment of a novel hybrid machine learning-based landslide susceptibility mapping model in the Darjeeling Himalayas - Abhik Saha; Vasanta Govind Kumar Villuri; Ashutosh Bhardwaj (Stochastic Environmental Research and Risk Assessment, 2025)

A combination of morphological, biochemical and structural responses is required for desiccation tolerance in Selaginella repanda - Hosahalli Somasundara Rudresh; Neeragunda Shivaraj Yathisha; Sakrepatna Lakshminarayana Vaishnavi; Hulikal Shivashankara Santosh Kumar; Sudisha Jogaiah; Ramasandra Govind Sharathchandra (Physiology and Molecular Biology of Plants, 2025)

Structural and maturity evolution of lignite using Raman spectroscopy and organic petrology of the Barmer basin, Rajasthan, India - Om Prakash Kumar; P. Gopinathan; Amiya S. Naik; Pramod K. Rajak; Govind Kumar; Neeraj K. Upadhayay; Amit Karmakar; T. Subramani (Environmental Geochemistry and Health, 2025)

Revolutionizing Parkinson’s treatment: Harnessing the potential of intranasal nanoemulsions for targeted therapy - Gulshan Sharma; Karan Wadhwa; Shobhit Kumar; Govind Singh; Rakesh Pahwa (Drug Delivery and Translational Research, 2025)

Integrated Nutrient Management Approaches in Strawberry for Higher Yield and Soil Nutrients in Semi-arid Conditions of Bundelkhand Region of Central India - Rajeev Kumar; Gaurav Sharma; Ranjit Pal; Ghanshyam Abrol; Shivali Sharma; Govind Vishwakarma; Sukanya Misra (Applied Fruit Science, 2025)

Polypharmacology and Neuroprotective Effects of Gingerol in Alzheimer’s Disease - Sakthi Priyadarshini; Keshav Goyal; Roopashree R; Saurabh Gupta; Aatreyi Roy; Ritabrata Biswas; Sandeep Patra; Payal Chauhan; Karan Wadhwa; Govind Singh; Mehnaz Kamal; Danish Iqbal; et al. (Molecular Neurobiology, 2025)

Reactor design and process optimization in chemical looping combustion: Insights into fuel types, oxygen carriers, and process design - Raghvendra Kumar Gupta; Krish Jain; Hari Govind; Natarajan Rajamohan; Iyman Abrar (Journal of Environmental Chemical Engineering, 2025)

Isolation, characterization, HPLC quantification, in-vitro and in-silico evaluations of coumarins and coumarolignans from Blighia unijugata stem with their chemotaxonomic significance - Clement Odunayo Ajiboye; Dorcas Olufunke Moronkola; Arfan Khalid; Akinbo Akinwumi Adesomoju; Sagar S. Bhayye; Yogesh P. Bharitkar; Govind Yadav; Mahendra Kumar Verma (Biochemical Systematics and Ecology, 2025)

Unlocking the Neuroprotective Potential of Silymarin: A Promising Ally in Safeguarding the Brain from Alzheimer’s Disease and Other Neurological Disorders - Abdulmajeed G. Almutary; M. Yasmin Begum; Ayesha Siddiqua; Saurabh Gupta; Payal Chauhan; Karan Wadhwa; Govind Singh; Danish Iqbal; Gopalakrishnan Padmapriya; Sanjay Kumar; Navin Kedia; Rajni Verma; et al. (Molecular Neurobiology, 2025)

Retraction Note: An update on pathophysiology and treatment of sports-mediated brain injury - Sunishtha Kalra; Rittu Banderwal; Kaushal Arora; Sandeep Kumar; Govind Singh; Pooja A. Chawla; Tapan Behl; Aayush Sehgal; Sukhbir Singh; Saurabh Bhatia; Ahmed Al-Harrasi; Lotfi Aleya; et al. (Environmental Science and Pollution Research, 2025)

Unveiling the Involvement of Herpes Simplex Virus-1 in Alzheimer’s Disease: Possible Mechanisms and Therapeutic Implications - Payal Chauhan; M. Yasmin Begum; Bayapa Reddy Narapureddy; Saurabh Gupta; Karan Wadhwa; Govind Singh; Rohit Kumawat; Naveen Sharma; Suhas Ballal; Saurabh Kumar Jha; Mosleh Mohammad Abomughaid; Dheepak B; et al. (Molecular Neurobiology, 2025)

Response of Bioformulations and Inorganic Fertilizers for Productivity, Quality, and Soil Microbial Activity of Banana in the Subtropics - Dinesh Kumar; Govind Kumar; K. K. Srivastava; Vinod Kumar Singh; Sumit K. Soni (Applied Fruit Science, 2025)

A framework for implementation of environmental flow requirements through community perceptions – the case of Bargi Dam, Jabalpur District, Madhya Pradesh - Govind M. P.; Rama Umesh Pandey; Pradeep Kumar (Hydrological Sciences Journal, 2025)

P–T Evolution of Paleoproterozoic Dangoli Pelitic Gneisses, Baijnath Klippe, NW Himalaya: Insights From the Geochemistry and Zircon U–Pb Geochronology - Mallickarjun Joshi; Shubham Patel; Biraja P. Das; Govind Oinam; Tanya Srivastava; Alok Kumar (Island Arc, 2025)
The Cenozoic Himalayan orogeny resulted from the continental collision between the Tibetan block and the northern Indian Precambrian shield. The latter, replete with evidence of Columbian supercontinent assembly, likely comprised the north Indian continental margin that was reworked mechanically and thermally during the Himalayan orogeny, and still survives as Precambrian vestiges in the Himalaya. Parts of this Paleoproterozoic crust, which now occur as nappes and klippen, were tectonically transported by the Main Central Thrust southwards over the Lesser Himalayan sedimentaries during the orogeny. The Absence of Columbian metamorphic signatures in these thrust sheets has intrigued geologists for long. We present evidence for a Middle Orosirian metamorphic event from the pelitic gneisses of the Almora Group in the Baijnath Klippe from NW Himalaya. The physical conditions of metamorphism have been inferred using mineral chemistry, bulk‐rock chemistry, and phase section modeling using Perple_X software in the MnNKCFMASHT model system. Zircon U–Pb geochronology for the Dangoli pelitic gneisses yielded a robust upper intercept at 1891 ± 12.82 Ma. The P–T phase diagram indicates that the peak mineral assemblage stabilized in the P–T range of 0.41–0.46 GPa and 675°C–700°C suggesting upper amphibolite facies metamorphism. Integrated metamorphic and geochronological results indicate that the Dangoli pelitic gneisses were derived by muscovite dehydration melting of metasediments during the peak metamorphism related to syn‐collisional setting broadly coeval with the Paleoproterozoic magmatism during the Columbia supercontinent assembly. The evidence for definite involvement of Paleoproterozoic high‐grade metamorphic rocks of the northern Indian shield in the Himalayan orogeny is being documented.

Unraveling the Stability of Sugarcane Clones Using Multivariate Stability Models for Cane Yield and Quality Under Subtropical Climates - Mintu Ram Meena; Ravinder Kumar; R. Karuppaiyan; Neeraj Kulshreshtha; Manohar Lal Chhabra; Amaresh; Gopalareddy Krishnappa; Aswini Nunavath; K. Mohanraj; Perumal Govindaraj; Govind Hemaprabha (Sugar Tech, 2024)

Investigating the Potential Therapeutic Mechanisms of Puerarin in Neurological Diseases - Payal Chauhan; Karan Wadhwa; Richa Mishra; Saurabh Gupta; Fuzail Ahmad; Mehnaz Kamal; Danish Iqbal; Mohammed Alsaweed; Mohana Vamsi Nuli; Mosleh Mohammad Abomughaid; Abdulmajeed G. Almutary; Prabhu Chandra Mishra; et al. (Molecular Neurobiology, 2024)

NIR Light-triggered Green Emitting Perovskite-based Phosphor for Optical Thermometry and Future Molecular Logic Gate Applications - Ishant Kumar; Avinash Kumar; Sandeep Kumar; Govind B. Nair; H. C. Swart; Arvind K. Gathania (Journal of Fluorescence, 2024)

First report of 'Candidatus Phytoplasma trifolii' related strain causing witches’ broom disease of black cumin (Nigella sativa L.) in India - Shivani Gupta; Hemavati Ranebennur; Sushil K. Singh; Gagan Kumar; V. Singh; J.K. Yadav; Govind P. Rao (Physiological and Molecular Plant Pathology, 2024)

Evaluating exhaust emissions from heterogeneous car fleet through real-time field-generated dataset - Abhinav Pandey; Govind Pandey; Rajeev Kumar Mishra (Atmospheric Pollution Research, 2024)

Repositioning the existing drugs for neuroinflammation: a fusion of computational approach and biological validation to counter the Parkinson’s disease progression - Harshita Tiwari; Amit Kumar; Manas Ranjan Barik; Harjot Kaur; Shubham Mahajan; Monu Kumar Shukla; Monika Gupta; Govind Yadav; Amit Nargotra (Molecular Diversity, 2024)

Damage assessment of buildings due to land subsidence in Joshimath town of Northwestern Himalaya, India - Ajay Chourasia; Mickey Mecon Dalbehera; Ashish Kapoor; Kishor S. Kulkarni; Govind Gaurav; Satyavrat Singh; R. Pradeep Kumar (Natural Hazards, 2024)

Distribution maps depicting geographical prevalence of rapeseed-mustard diseases in India - Prabhu Dayal Meena; Pramod Kumar Rai; Govind Singh Saharan (Indian Phytopathology, 2024)

Salicylic acid and thiourea ameliorated adverse effects of salinity and drought-induced changes in physiological traits and yield of wheat - Taramani Yadav; R. K. Yadav; Gajender Yadav; Ashwani Kumar; Govind Makarana (Cereal Research Communications, 2024)

Assessment of Strawberry to Integrated Nutrient Management for Different Yield Attributes and Quality Parameters - Govind Vishwakarma; Abhishek Kumar Shukla; Fathema Zaman; Ashutosh Singh; Sharwan Kumar Shukla (Applied Fruit Science, 2024)

Detection of NO2 at ppm-level using Al-doped CeO2 based gas sensor with high sensitivity and selectivity at room temperature - D. Kanchan Kumar; P. Bharathi; A. Govind; J. Archana; M. Navaneethan; S. Harish (Journal of Environmental Chemical Engineering, 2024)

Achieving Sustainable Development Goals: A Case Study of Dalmia Bharat Sugar & Industries Limited - Priyanka Singh; S. Solomon; Pankaj Rastogi; Kuldeep Kumar; Govind P. Rao (Sugar Tech, 2024)

Chlamydomonas as a model system for studying the relevance of plant genes for their involvement in multiple individual and combined stresses: a study unravelling PgCuZnSOD and PgAPX gene functions - H. M. Mamrutha; Geetha Govind; Hema Ramanna; Radha Sivarajan Sajeevan; A. N. Lokesha; Muthappa Senthil-Kumar; Karaba N. Nataraja (Plant Physiology Reports, 2024)

Emission performance evaluation of urban passenger car fleet through field investigation data in a megacity - Abhinav Pandey; Govind Pandey; Rajeev Kumar Mishra (Environmental Science and Pollution Research, 2024)

Exploring machine learning and statistical approach techniques for landslide susceptibility mapping in Siwalik Himalayan Region using geospatial technology - Abhik Saha; Lakshya Tripathi; Vasanta Govind Kumar Villuri; Ashutosh Bhardwaj (Environmental Science and Pollution Research, 2024)

Mediation effect of diversity and availability of high transit service on transit oriented development and spread of COVID-19 - Rupali Khare; Vasanta Govind Kumar Villuri; Satish Kumar; Devarshi Chaurasia (Environment, Development and Sustainability, 2023)

Predicting the future landscape of Dhanbad District: an analysis of land-use change and urban sprawl through cloud computing and neural networks - Vivek Singh; Purnendu Sardar; Sukha Ranjan Samadder; Dheeraj Kumar; Vasant Govind K. Villuri (Environment, Development and Sustainability, 2023)

Sex differences in cognitive function among people with HIV-1 clade C infection in Northern India - Anchal Sharma; Manju Mohanty; Teddy Salan; Deepika Aggarwal; Lissa Mandell; Deborah L. Jones; Kristopher Arheart; Aman Sharma; Sameer Vyas; Paramjeet Singh; Varan Govind; Mahendra Kumar (Journal of NeuroVirology, 2023)

Biological approaches for E-waste management: A green-go to boost circular economy - Rashmi Dixit; Sunil Kumar; Govind Pandey (Chemosphere, 2023)

Design of Low-Stress robust silicon and Silicon-Carbide anode with high areal capacity and high energy density for Next-Generation Lithium-Ion batteries - Manoj Gautam; Govind Kumar Mishra; Mohammad Furquan; K. Bhawana; Dhruv Kumar; Sagar Mitra (Chemical Engineering Journal, 2023)

First report of ‘Candidatus Phytoplasma australasia’ related strain associated with opium poppy phyllody and stunting in India - Sushil Kumar Singh; R. K. Mishra; M. Gurivi Reddy; S. N. Rahul; Carmine Marcone; Govind P. Rao (Australasian Plant Pathology, 2023)

Comparative analysis of desiccation tolerance in Oeosporangium elegans and Mickelopteris cordata - Hosahalli Somasundara Rudresh; Thippesh Divyashree; Neeragunda Shivaraj Yathisha; Venkatesha Dwarakanath; Hulikall Shivashankara Santhosh Kumar; Ramasandra Govind Sharathchandra (Vegetos, 2023)

Tear-based MMP-9 detection: A rapid antigen test for ocular inflammatory disorders using vanadium disulfide nanowires assisted chemi-resistive biosensor - Tanmoya Nemai Ghosh; Dinesh Rotake; Saurabh Kumar; Inderjeet Kaur; Shiv Govind Singh (Analytica Chimica Acta, 2023)

Geophysical and geostatistical assessment of groundwater and soil quality using GIS, VES, and PCA techniques in the Jaipur region of Western India - Jabbar Khan; Govind Gupta; Naveen Kumar Singh; Vivek Narayan Bhave; Vinay Bhardwaj; Pallavi Upreti; Rani Singh; Amarendra Kumar Sinha (Environmental Science and Pollution Research, 2023)

Comparative Expression Profile of Genes Encoding Intolerant Proteins in Bread vs. Durum Wheat During Grain Development - Megha Kaushik; Ekta Mulani; Anju Mahendru-Singh; Govind Makharia; Sumedha Mohan; Pranab Kumar Mandal (Journal of Plant Growth Regulation, 2023)

Nanoparticle-mediated bioremediation as a powerful weapon in the removal of environmental pollutants - Parul Chaudhary; Lukman Ahamad; Anuj Chaudhary; Govind Kumar; Wen-Juan Chen; Shaohua Chen (Journal of Environmental Chemical Engineering, 2023)

Semen characteristics and artificial insemination in dromedary camels - Govind Narayan Purohit; Sumant Vyas; Vishal Yadav; Satish Nain; Ashok Kumar Chaudhary; Amit Kumar; Sandeep Dholpuria; Chandra Shekhar Saraswat (Small Ruminant Research, 2023)

Tectonic evolution of the neoproterozoic tusham ring complex, Northwestern India: Constraints from geochemistry and zircon U Pb geochronology, and implications for Rodinia supercontinent history - A. Krishnakanta Singh; Naveen Kumar; Sun-Lin Chung; Hao-Yang Lee; M. Santosh; Radhika Sharma; Naresh Kumar; R.K. Bikramaditya; Govind Oinam; Nongmaithem Lakhan (Lithos, 2023)

Hexavalent chromium-reducing plant growth-promoting rhizobacteria are utilized to bio-fortify trivalent chromium in fenugreek by promoting plant development and decreasing the toxicity of hexavalent chromium in the soil - Sumit K. Soni; Govind Kumar; Anju Bajpai; Rakshapal Singh; Yashi Bajapi; Laxmi; Sudeep Tiwari (Journal of Trace Elements in Medicine and Biology, 2023)

Transcription factors controlling the expression of oxidative stress associated genes in rice (Oryza sativa L.) - D. Sujitha; H. G. Jalendra Kumar; Garima Thapliayal; Garima Pal; P. A. Vanitha; Akshay Uttarkar; Mahesh Patil; B. H. Rajashekar Reddy; Vidya Niranjan; Usha Rayalcheruvu; Geetha Govind; M. Udayakumar; et al. (Plant Biotechnology Reports, 2023)

Air-permeable redox mediated transcutaneous CO2 sensor - Preety Ahuja; Sanjeev Kumar Ujjain; Radovan Kukobat; Koki Urita; Isamu Moriguchi; Ayumi Furuse; Yoshiyuki Hattori; Keisaku Fujimoto; Govind Rao; Xudong Ge; Thelma Wright; Katsumi Kaneko (Chemical Engineering Journal, 2023)

Design and implementation of earthquake early warning dissemination mobile app for Uttarakhand (India) - Govind Rathore; Kamal; Ashok Kumar; R. S. Jakka; M. L. Sharma (Journal of Seismology, 2023)

Epinephrine facilitates the growth of T cell lymphoma by altering cell proliferation, apoptosis, and glucose metabolism - Rajan Kumar Tiwari; Shiv Govind Rawat; Vishal Kumar Gupta; Pradip Kumar Jaiswara; Pratishtha Sonker; Santosh Kumar; Vibhav Gautam; Manoj K. Mishra; Ajay Kumar (Chemico-Biological Interactions, 2023)

Multilocus gene-based characterization of peanut witches’ broom related phytoplasma strain associated with flower malformation of papaya in India - Priyam Panda; Sushil Kumar Singh; Smriti Mall; Govind Pratap Rao (Indian Phytopathology, 2022)

An in situ exploratory analysis of diesel cars’ emission: way forward on policy evaluation - Abhinav Pandey; Govind Pandey; Rajeev Kumar Mishra (Environmental Science and Pollution Research, 2022)

Australasian Plant Pathology: Disease note Identification of ‘Candidatus Phytoplasma asteris’ related strains associated with three medicinal plants in India - Surabhi Mitra; Govind Pratap Rao; Manoj Kumar Kalita; Amar Bahadur (Australasian Plant Pathology, 2022)

A holistic approach for understanding the status of water quality and causes of its deterioration in a drought-prone agricultural area of Southeastern India - Prabhakara Chowdary Pathakamuri; Vasanta Govind Kumar Villuri; Srinivas Pasupuleti; Ashes Banerjee; Akella Satya Venkatesh (Environmental Science and Pollution Research, 2022)

Characterization and distribution of phytoplasma strains associated with temperate stone fruits and their possible natural reservoirs in the north-western Himalayan states of India - Yapalahalli Sathyanarayanappa Shreenath; Ashok Kumar Singh; Pasumarthi Venkata Dinesh Kumar; Santosh Watpade; Krishna Pratap Singh; Govind Pratap Rao (European Journal of Plant Pathology, 2022)

Identification of ‘Ca. Phytoplasma asteris’, banana bunchy top virus and banana streak MY virus associated with Champa and Sabri banana cultivars in Tripura, a North Eastern state of India - Surabhi Mitra; Prasenjit Debnath; Richa Rai; Nishant Srivastava; Govind Pratap Rao; Virendra Kumar Baranwal (European Journal of Plant Pathology, 2022)

Phosphodiesterase 5 inhibitor sildenafil potentiates the antitumor activity of cisplatin by ROS-mediated apoptosis: a role of deregulated glucose metabolism - Shiv Govind Rawat; Rajan Kumar Tiwari; Pradip Kumar Jaiswara; Vishal Kumar Gupta; Pratishtha Sonker; Naveen Kumar Vishvakarma; Santosh Kumar; Chandramani Pathak; Vibhav Gautam; Ajay Kumar (Apoptosis, 2022)

First report of cherry tomato leaf curl virus and associated DNA satellite in Daucus carota in India - P. V. Dinesh Kumar; Richa Rai; Virendra Kumar Baranwal; Shailendra Kumar; Govind Pratap Rao; Amish Kumar Sureja; Rajendra Prasad Pant (Journal of Plant Pathology, 2022)

Molecular characterization and genetic diversity studies of Indian soybean (Glycine max (L.) Merr.) cultivars using SSR markers - S. P. Jeevan Kumar; C. Susmita; K. V. Sripathy; Dinesh K. Agarwal; Govind Pal; Arvind Nath Singh; Sanjay Kumar; Abhishek Kumar Rai; Jesus Simal-Gandara (Molecular Biology Reports, 2022)
Background The genetic base of soybean cultivars in India has been reported to be extremely narrow, due to repeated use of few selected and elite genotypes as parents in the breeding programmes. This ultimately led to the reduction of genetic variability among existing soybean cultivars and stagnation in crop yield. Thus in order to enhance production and productivity of soybean, broadening of genetic base and exploring untapped valuable genetic diversity has become quite indispensable. This could be successfully accomplished through molecular characterization of soybean genotypes using various DNA based markers. Hence, an attempt was made to study the molecular divergence and relatedness among 29 genotypes of soybean using SSR markers. Methods and results A total of 35 SSR primers were deployed to study the genetic divergence among 29 genotypes of soybean. Among them, 14 primer pairs were found to be polymorphic producing a total of 34 polymorphic alleles; and the allele number for each locus ranged from two to four with an average of 2.43 alleles per primer pair. Polymorphic information content (PIC) values of SSRs ranged from 0.064 to 0.689 with an average of 0.331. The dendrogram constructed based on dissimilarity indices clustered the 29 genotypes into two major groups and four sub-groups. Similarly, principal coordinate analysis grouped the genotypes into four major groups that exactly corresponded to the clustering of genotypes among four sub-groups of dendrogram. Besides, the study has reported eight unique and two rare alleles that could be potentially utilized for genetic purity analysis and cultivar identification in soybean. Conclusion In the present investigation, two major clusters were reported and grouping of large number of genotypes in each cluster indicated high degree of genetic resemblance and narrow genetic base among the genotypes used in the study. With respect to the primers used in the study, the values of PIC and other related parameters revealed that the selected SSR markers are moderately informative and could be potentially utilized for diversity analysis of soybean. The clustering pattern of dendrogram constructed based on SSR loci profile displayed good agreement with the cultivar’s pedigree information. High level of genetic similarity observed among the genotypes from the present study necessitates the inclusion of wild relatives, land races and traditional cultivars in future soybean breeding programmes to widen the crop gene pool. Thus, hybridization among diverse gene pool could result in more heterotic combinations ultimately enhancing genetic gain, crop yield and resistance to various stress factors.

RETRACTED ARTICLE: An update on pathophysiology and treatment of sports-mediated brain injury - Sunishtha Kalra; Rittu Banderwal; Kaushal Arora; Sandeep Kumar; Govind Singh; Pooja A. Chawla; Tapan Behl; Aayush Sehgal; Sukhbir Singh; Saurabh Bhatia; Ahmed Al-Harrasi; Lotfi Aleya; et al. (Environmental Science and Pollution Research, 2022)

Hydro-geochemical evolution of groundwater and associated human health risk in River Sone subbasin of Middle-Gangetic floodplain, Bihar, India - Ajay Govind Bhatt; Anand Kumar; Shatrunjay Kumar Singh (Arabian Journal of Geosciences, 2022)

Bilinear elasto-dynamical response of SDOF system under sinusoidal loading - Govind Mohan; Umesh Kumar Pandey (Innovative Infrastructure Solutions, 2022)

Impact of climate change on stormwater drainage in urban areas - Satish Kumar; Ankit Agarwal; Abinesh Ganapathy; Vasant Govind Kumar Villuri; Srinivas Pasupuleti; Dheeraj Kumar; Deo Raj Kaushal; Ashwin Kumar Gosain; Bellie Sivakumar (Stochastic Environmental Research and Risk Assessment, 2022)

Constructed wetland management in urban catchments for mitigating floods - Satish Kumar; Ankit Agarwal; Vasant Govind Kumar Villuri; Srinivas Pasupuleti; Dheeraj Kumar; Deo Raj Kaushal; Ashwin Kumar Gosain; Axel Bronstert; Bellie Sivakumar (Stochastic Environmental Research and Risk Assessment, 2021)

Screening of wheat germplasm for terminal heat tolerance under hyper-arid conditions - Vishnu Prakash Agarwal; Narendra Kumar Gupta; Sunita Gupta; Govind Singh (Cereal Research Communications, 2021)

Casein (CSN) gene variants and parity affect the milk protein traits in crossbred (Bos taurus x Bos indicus) cows in sub-tropical climate - Govind Mohan; Anshuman Kumar; Suhail Hakeem Khan; N. Anand Kumar; Suman Kapila; S. S. Lathwal; Monika Sodhi; S. K. Niranjan (Tropical Animal Health and Production, 2021)

First report of ‘Candidatus Phytoplasma asteris’ associated with flat stem disease of spinach (Spinacia oleracea L.) in India - Shweta Kumari; Krishnan Nagendran; Rajesh Kumar; Koshlendra Kumar Pandey; Jagdish Singh; Govind Pratap Rao (Journal of Plant Pathology, 2021)

First report of 16SrXI-B subgroup phytoplasma in sapota showing flattened stem disease in India - Shailender Kumar; Jitender Singh; Virendra Kumar Baranwal; Govind Pratap Rao (Journal of Plant Pathology, 2021)

Measurement of transit-oriented development (TOD) using GIS technique: a case study - Rupali Khare; Vasanta Govind Kumar Villuri; Devarshi Chaurasia; Supriya Kumari (Arabian Journal of Geosciences, 2021)

Multilocus sequence analysis of a ‘Candidatus Phytoplasma australasia’-related strain associated with peanut little leaf disease in India - Surabhi Mitra; Manish Kumar; Karuba Vemana; Karla Saratbabu; Antony Masilamani Johnson; Swarup Mishra; Carmine Marcone; Govind P. Rao (Journal of Plant Pathology, 2021)

Mussaenda erythrophylla: A new host of ‘Candidatus Phytoplasma asteris’ in India - Priyam Panda; Tasou Rihne; Ashok Kumar Singh; Govind Pratap Rao (Indian Phytopathology, 2020)

Identification of phytoplasma in six fruit crops in India - Govind Pratap Rao; Ashutosh Rao; Manish Kumar; Hemavati Ranebennur; Surabhi Mitra; Ashok Kumar Singh (European Journal of Plant Pathology, 2020)

Lysophosphatidic acid promotes survival of T lymphoma cells by altering apoptosis and glucose metabolism - Vishal Kumar Gupta; Pradip Kumar Jaiswara; Pratishtha Sonker; Shiv Govind Rawat; Rajan Kumar Tiwari; Ajay Kumar (Apoptosis, 2020)

Assessment of particulate matter, metals of toxicological concentration, and health risk around a mining area, Odisha, India - Akhilesh Kumar Yadav; Sunil Kumar Sahoo; Jay Singh Dubey; Aerattukkara Vinod Kumar; Govind Pandey; Raj Mangal Tripathi (Air Quality, Atmosphere & Health, 2019)

Correction to: Identification and functional validation of a unique set of drought induced genes preferentially expressed in response to gradual water stress in peanut - Geetha Govind; Harshavardhan Vokkaliga ThammeGowda; Patricia Jayaker Kalaiarasi; Dhanalakshmi Ramchandra Iyer; Senthil Kumar Muthappa; Sreenivasulu Nese; Udaya Kumar Makarla (Molecular Genetics and Genomics, 2019)

New Efficient Natural Leafhopper Vectors of Sugarcane Grassy Shoot Phytoplasma in India - Ajay K. Tiwari; Shailender Kumar; Smriti Mall; Vikas Jadon; Govind P. Rao (Sugar Tech, 2017)

Arterial-ventricular and interventricular interaction in isolated post-capillary and combined pulmonary hypertension in severe mitral stenosis - Ashwin Venkateshvaran; Srikanth Sola; Satish Chandra Govind; Pravat Kumar Dash; Sagar Vyavahare; Lars H. Lund; Bé la Merkely; Anikó Ilona Nagy; Aristomenis Manouras (European Journal of Applied Physiology, 2016)

Global Fluoride Occurrence, Available Technologies for Fluoride Removal, and Electrolytic Defluoridation: A Review - Neha Mumtaz; Govind Pandey; Pawan Kumar Labhasetwar (Critical Reviews in Environmental Science and Technology, 2015)

Global Fluoride Occurrence, Available Technologies for Fluoride Removal and Electrolytic Defluoridation: A Review - Neha Mumtaz; Govind Pandey; Pawan Kumar Labhasetwar (Critical Reviews in Environmental Science and Technology, 2015)

Identification of a novel phytoplasma (16Sr XIV-A subgroup) associated with little leaf and witches’ broom of Cannabis sativa L. ssp. sativa and C. sativa L. ssp. indica in India - Savita Chaube; Shailender Kumar; Durgesh Dubey; Ajay Kumar Tiwari; Parmatma Prasad Upadhyaya; Govind Pratap Rao (Phytoparasitica, 2015)

Comparative Pharmacokinetic Study of Mangiferin After Oral Administration of Pure Mangiferin and US Patented Polyherbal Formulation to Rats - Ananth Kumar Kammalla; Mohan Kumar Ramasamy; Jyothi Inampudi; Govind Prasad Dubey; Aruna Agrawal; Ilango Kaliappan (AAPS PharmSciTech, 2015)

Identification of sugarcane grassy shoot-associated phytoplasma and one of its putative vectors in India - Govind Pratap Rao; Madhupriya; Ajay Kumar Tiwari; Shailendra Kumar; Virendra Kumar Baranwal (Phytoparasitica, 2014)

Effects of explant age, germination medium, pre-culture parameters, inoculation medium, pH, washing medium, and selection regime on Agrobacterium-mediated transformation of tomato - Govind Kumar Rai; Neha Prakash Rai; Sanjeev Kumar; Akhilesh Yadav; Sushma Rathaur; Major Singh (In Vitro Cellular & Developmental Biology - Plant, 2012)

Ethanol Production Through Saccharomyces Based Fermentation Using Apple Pomace Amended with Molasses - Shyam Kanwar; Govind Kumar; Manvika Sahgal; Anupama Singh (Sugar Tech, 2012)

A Rapid Two-Step Bioremediation of the Anthraquinone Dye, Reactive Blue 4 by a Marine-Derived Fungus - Ashutosh Kumar Verma; Chandralata Raghukumar; Rajesh Ramnath Parvatkar; Chandrakant Govind Naik (Water, Air, & Soil Pollution, 2012)

In vitro propagation of spine gourd (Momordica dioica Roxb.) and assessment of genetic fidelity of micropropagated plants using RAPD analysis - Govind Kumar Rai; Major Singh; Neha Prakash Rai; D. R. Bhardwaj; Sanjeev Kumar (Physiology and Molecular Biology of Plants, 2012)

A Simple and Non-destructive Method of Direct-PCR for Plant Systems - R. Sharma; Vinod Kumar; T. Mohapatra; Vikas Khandelwal; Govind K. Vyas (Journal of Plant Biology, 2012)

Fuelwood consumption in two tribal villages of the Nanda Devi Biosphere Reserve of the Indian Himalaya and strategies for fuelwood sustainability - Govind S. Rajwar; Munesh Kumar (Environment, Development and Sustainability, 2011)

Assessment of trace metal toxicity in soils of Raniganj Coalfield, India - Supriyo Kumar Das; Govind J. Chakrapani (Environmental Monitoring and Assessment, 2011)

Four marine-derived fungi for bioremediation of raw textile mill effluents - Ashutosh Kumar Verma; Chandralata Raghukumar; Pankaj Verma; Yogesh S. Shouche; Chandrakant Govind Naik (Biodegradation, 2010)

Biogeochemical records of paleoenvironmental changes in Nainital Lake, Kumaun Himalayas, India - Preetam Choudhary; Joyanto Routh; Govind J. Chakrapani; Bhishm Kumar (Journal of Paleolimnology, 2009)

Diversity analysis of Capparis decidua (Forssk.) Edgew. using biochemical and molecular parameters - Govind K. Vyas; R. Sharma; Vinod Kumar; T. B. Sharma; V. Khandelwal (Genetic Resources and Crop Evolution, 2009)

Identification and functional validation of a unique set of drought induced genes preferentially expressed in response to gradual water stress in peanut - Geetha Govind; Vokkaliga ThammeGowda Harshavardhan; Jayaker Kalaiarasi Patricia; Ramachandra Dhanalakshmi; Muthappa Senthil Kumar; Nese Sreenivasulu; Makarla Udayakumar (Molecular Genetics and Genomics, 2009)

Identification and functional validation of a unique set of drought induced genes preferentially expressed in response to gradual water stress in peanut - Geetha Govind; Harshavardhan Vokkaliga ThammeGowda; Patricia Jayaker Kalaiarasi; Dhanalakshmi Ramchandra Iyer; Senthil Kumar Muthappa; Sreenivasulu Nese; Udaya Kumar Makarla (Molecular Genetics and Genomics, 2009)

Functional characterization of Nicotiana benthamiana homologs of peanut water deficit-induced genes by virus-induced gene silencing - M. Senthil-Kumar; Geetha Govind; Li Kang; Kirankumar S. Mysore; M. Udayakumar (Planta, 2007)